Combined cell-surface display- and secretion-based strategies for production of cellulosic ethanol with Saccharomyces cerevisiae. Issue 1 (December 2015) - Liu, Zhuo; Inokuma, Kentaro; Ho, Shih-Hsin; Haan, Riaan; Hasunuma, Tomohisa; Zyl, Willem; Kondo, Akihiko
Abstract Background EngineeringSaccharomyces cerevisiae to produce heterologous cellulases is considered as a promising strategy for production of bioethanol from lignocellulose. The production of cellulase is usually pursued by one of the two strategies: displaying enzyme on the cell surface or secreting enzyme into the medium. However, to our knowledge, the combination of the two strategies in a yeast strain has not been employed. Results In this study, heterologous endoglucanase (EG) and cellobiohydrolase I (CBHI) were produced in aβ -glucosidase displayingS. cerevisiae strain using cell-surface display, secretion, or a combined strategy. Strains EG-D-CBHI-D and EG-S-CBHI-S (with both enzymes displayed on the cell surface or with both enzymes secreted to the surrounding medium) showed higher ethanol production (2.9 and 2.6 g/L from 10 g/L phosphoric acid swollen cellulose, respectively), than strains EG-D-CBHI-S and EG-S-CBHI-D (with EG displayed on cell surface and CBHI secreted, or vice versa). After 3-cycle repeated-batch fermentation, the cellulose degradation ability of strain EG-D-CBHI-D remained 60 % of the 1st batch, at a level that was 1.7-fold higher than that of strain EG-S-CBHI-S. Conclusions This work demonstrated that placing EG and CBHI in the same space (on the cell surface or in the medium) was favorable for amorphous cellulose-based ethanol fermentation. In addition, the cellulolytic yeast strain that produced enzymes by the cell-surface display strategy performed better in cell-recycle batch fermentation compared to strains producing enzymes via the secretion strategy.